2003
DOI: 10.1093/nar/gng038
|View full text |Cite
|
Sign up to set email alerts
|

A simple and cost-effective method for producing small interfering RNAs with high efficacy

Abstract: Small interfering RNAs (siRNAs) are powerful RNA interference (RNAi) reagents for directed post- transcriptional gene silencing. Exogenous siRNA is frequently used in RNAi studies. However, due to profound differences in the activity of siRNAs targeted to different regions of a gene, several reagents may have to be screened for optimal activity. This approach is expensive due to the cost of chemical synthesis of RNAs. We report a technically simple, quick and cost-effective method for the production of siRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 26 publications
2
37
0
1
Order By: Relevance
“…The criteria described by Sohail et al (2003) and the computer programme available at http://www.promega.com/siRNADesigner/ program/ were used to design siRNA. The T7 RiboMAX Express RNAi System Kit (Promega, Madison, WI, USA) was used to synthesise siRNA.…”
Section: Methodsmentioning
confidence: 99%
“…The criteria described by Sohail et al (2003) and the computer programme available at http://www.promega.com/siRNADesigner/ program/ were used to design siRNA. The T7 RiboMAX Express RNAi System Kit (Promega, Madison, WI, USA) was used to synthesise siRNA.…”
Section: Methodsmentioning
confidence: 99%
“…The polymerase produces individual sense and antisense siRNA strands that form siRNAs when annealed [34,173,206]. However, the purity and specificity using enzymatic synthesis is variable [36].…”
Section: Chemically Synthesized Sirnamentioning
confidence: 99%
“…Transcription is generated from short double stranded oligo cassettes containing the promoter sequence upstream of the siRNA template sequence that is to be transcribed [34,173]. Transcription begins and terminates at specific initiation and termination sequences, determined by the promoter [40].…”
Section: Chemically Synthesized Sirnamentioning
confidence: 99%
“…These investigators further demonstrated that the presence of triphosphates on the 59 end of T7 transcripts is required for interferon induction, since the treatment of T7 transcripts with phosphatase could abrogate this effect. Sohail et al (2003) reported an alternative approach for producing a desired siRNA sequence using T7 polymerase in vitro transcription followed by transcript digestion by deoxyribozymes, which are known as ''DNAzymes'' or catalytic DNA. The cleavage of RNA by DNAzymes occurs between two specific nucleotides, and the requirement for this dinucleotide sequence is different for different DNAzyme groups, making them flexible tools for digesting a variety of sequences (Breaker and Joyce 1994;Feldman and Sen 2001).…”
Section: In Vitro Transcription and Enzymatic Digestionmentioning
confidence: 99%